2000
DOI: 10.1111/1468-0084.00187
|View full text |Cite
|
Sign up to set email alerts
|

Bootstrap and Asymptotic Tests of Long‐run Relationships in Cointegrated Systems

Abstract: Hypothesis testing on cointegrating vectors based on the asymptotic distributions of the test statistics are known to suffer from severe small sample size distortion. In this paper an alternative bootstrap procedure is proposed and evaluated through a Monte Carlo experiment, finding that the Type I errors are close to the nominal signficance levels but power might be not entirely adequate. It is then shown that a combined test based on the outcomes of both the asymptotic and the bootstrap tests will have both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…Previous simulation studies of bootstrap tests on co-integrating relations in VAR models include Fachin (2000), Gredenhoff and Jacobson (2001), and Omtzigt and Fachin (2006). Compared to these, the Monte Carlo simulation study reported here differs substantially.…”
Section: B4 Summary Of Results and Relation To Existing Literaturementioning
confidence: 89%
See 2 more Smart Citations
“…Previous simulation studies of bootstrap tests on co-integrating relations in VAR models include Fachin (2000), Gredenhoff and Jacobson (2001), and Omtzigt and Fachin (2006). Compared to these, the Monte Carlo simulation study reported here differs substantially.…”
Section: B4 Summary Of Results and Relation To Existing Literaturementioning
confidence: 89%
“…More specifically, Fachin (2000) considers empirical size and power of a bootstrap version of the Wald test, using a bootstrap generating process (BGP) based on restricted estimates and i.i.d. resampling of unrestricted residuals.…”
Section: B4 Summary Of Results and Relation To Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The relatively small sample size of available data is the main constraint that delimits the available techniques to be used to only a couple of them that can potentially provide more valuable results: the ARDL model (see for example, Caporale and Chui 1999;Boyd et al 2001) and the bootstraps technique (a combination of bootstraps on cointegration is provided by Fachin 2000). In this paper, the latter will not be included due to space limitations.…”
Section: Econometric Backgroundmentioning
confidence: 99%
“…Hence, the asymptotic LR test is consistent. Now, consider a restricted bootstrap for H 0 , as initially proposed in Fachin (2000), Gredenho¤ and Jacobson (2001) and later discussed in Fachin and Omzigt (2006). This bootstrap requires estimation of (14) under H 0 and then use the corresponding (restricted) estimates~ n and to generate the bootstrap sample as…”
Section: Preliminaries and Bootstrap Consistencymentioning
confidence: 99%